Requirement Model For School Online Examination System - Wahab, Abdul Rahman (2007)

(untitled)
The School Online Examination System for multiple-choice questions is an appropriate solution for School to manage the examination. This system offers a dynamic solution where it can save the time to prepare the examination papers, evaluate the examination automatically and paperless. This study was carried out in order to produce a requirement model for Online Examination System for Sekolah Menengah Sultan Abdul Halim. The Unified Modeling Language (UML) has been used in the research to design the requirement model of School Online Examination System. There are three main phases involved in the study, which are, define requirement, analyse requirement and validate requirement. Upon completion, a prototype was developed based on the model. In addition, the prototype of examination system is also used to validate the user's requirements. This study has concluded by summarising the overall results and achievements. There are some recommendations for future work also presented.